Correction: Flexible lipid nanomaterials studied by NMR spectroscopy. Issue 34 (19th August 2021) - Mallikarjunaiah, K. J.; Kinnun, Jacob J.; Petrache, Horia I.; Brown, Michael F.
Abstract : Correction for 'Flexible lipid nanomaterials studied by NMR spectroscopy' by K. J. Mallikarjunaiah et al., Phys. Chem. Chem. Phys., 2019, 21, 18422–18457, DOI: ; 10.1039/C8CP06179C .